Fun Handwashing and Training on Making Natural Handsanitizer - Eka Astuty; Elpira Asmin; Melda Yunita (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Regular hand washing is an important part of the WHO's COVID-19 prevention campaign and recent simulations show that much can be achieved in slowing the spread of the virus through increased hand washing. This is what underlies the community service activities located at LKSA ITTAQOLLAH as a simple step to cultivate hand washing culture while providing additional knowledge and skills to participants about making natural hand sanitizers. The preparatory stage of this activity is observing the location of the activity and managing the administration of the activity, as well as coordinating with the manager of LKSA ITTAQOLLAH. This community service activity is carried out by delivering counseling materials first. Counseling materials about the benefits of handwashing and the correct procedures for handwasing. The activity was continued with hands-on practice of handwasing, and ended with training on making natural hand sanitizers. The conclusion obtained after the implementation of this community service activity, is that the participants of the activity were very enthusiastic, the children participated in the activity from beginning to end. Increased knowledge about health in this case about how to wash hands with soap correctly and skills in this case the practice of making hand sanitizers are needed to improve the health status of children in LKSA ITTAQOLLAH.